Pendampingan Perpustakaan Nagari Situmbuk Melalui Pengolahan Bahan Pustaka - Sri Wahyuni; Rika Jufriazia Manita; Novia Yolanda Putri; Silvi Rahayu Ningsih; Sandi Marlianza (CV Yazri Aksara Nusantara, 2024)
The Nagari Library plays an important role in the development of community literacy at the nagari level. In library management activities to improve user services, classification activities become one of the important tasks. Classification is the systematic arrangement of library materials based on subjects that is useful for those who read or seek information. The community service conducted by the PKM team, consisting of lecturers and students from the Islamic Library and Information Science Study Program at UIN Mahmud Yunus Batusangkar, involved mentoring and processing collections at the Nagari Situmbuk Library. The outcome of the service activities carried out by the PKM team successfully assigned classification numbers to 600 book collections organized by discipline. The results of the mentoring and service conducted by the Lecturers and Students have a positive impact on the NagariSitumbuk Library and receive positive contributions from the village head and library managers. This is achieved through mentoring and guidance related to the proper and systematic management of the library, so that the books can be organized systematically and facilitate the search for users.